2012
DOI: 10.1021/la2048486
|View full text |Cite
|
Sign up to set email alerts
|

Charged Nanoparticle Dynamics in Water Induced by Scanning Transmission Electron Microscopy

Abstract: Using scanning transmission electron microscopy we image ~ 4 nm platinum nanoparticles deposited on an insulating membrane, where the membrane is one of two electron-transparent windows separating an aqueous environment from the microscope’s high vacuum. Upon receiving a relatively moderate dose of ~ 104 e/nm2, initially immobile nanoparticles begin to move along trajectories that are directed radially outward from the center of the field of view. With larger dose rates the particle motion becomes increasingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
116
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 24 publications
5
116
0
Order By: Relevance
“…Due to beam charging effects, it is possible that the silver nanorods could obtain net, positive charges. 21,28 As the nanorods are suspended in dielectric liquid, discharge into solution is expected. Based on the characteristic time scale for electrical discharge obtained from Maxwell's equations, the discharge time of a nanoparticle in a dilute electrolyte is on the order of nanoseconds.…”
Section: Modeling Of Nanoparticle Attachmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to beam charging effects, it is possible that the silver nanorods could obtain net, positive charges. 21,28 As the nanorods are suspended in dielectric liquid, discharge into solution is expected. Based on the characteristic time scale for electrical discharge obtained from Maxwell's equations, the discharge time of a nanoparticle in a dilute electrolyte is on the order of nanoseconds.…”
Section: Modeling Of Nanoparticle Attachmentmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Particle coalescence has been observed for haematite, iron oxyhydroxide, platinum-iron alloy, platinum, silver, and gold, allowing for assessment of coalescence features such as preferred particle orientations and kinetics. [12][13][14][24][25][26] When performing these experiments, care must be taken to avoid electron beam artifacts, such as specimen charging/reduction, flow effects, and bubbles, that can influence specimen behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18] The beam can be used to charge nanoparticles and affect their motion. 11 Microstructural changes 25 as well as formation and dynamics of bubbles or voids due to the beam have been reported. 20,[26][27][28] Amongst a variety of potential beam effects, 29 radiation chemistry, or interaction of ionizing radiation with the fluid medium, is critically important.…”
mentioning
confidence: 97%
“…It would not be possible to achieve nanoscale resolution at these thicknesses with transmission electron microscopy. Furthermore, although it has been suggested that Brownian motion should blur the images, this is not seen experimentally; instead, nanoparticles in close proximity to a membrane move several orders of magnitude slower than what would be expected for a bulk liquid (Ring & de Jonge, 2012;White et al, 2012;Verch et al, 2015).…”
Section: Model Of the Biotinylated Anti-her2 Affibody (Blue) Bindinmentioning
confidence: 94%